Integration of basal topographic cues and apical shear stress in vascular endothelial cells - Morgan, Joshua T. (2012)
In vivo, vascular endothelial cells (VECs) are anchored to the underlying stroma through a specialization of the extracellular matrix, the basement membrane (BM) which provides a variety of substratum associated biophysical cues that have been shown to regulate fundamental VEC behaviors. VEC function and homeostasis are also influenced by hemodynamic cues applied to their apical surface. How the combination of these biophysical cues impacts fundamental VEC behavior remains poorly studied. In the present study, we investigated the impact of providing biophysical cues simultaneously to the basal and apical surfaces of human aortic endothelial cells (HAECs). Anisotropically ordered patterned surfaces of alternating ridges and grooves and isotropic holed surfaces of varying pitch (pitch = ridge or hole width + intervening groove or planar regions) were fabricated and seeded with HAECs. The cells were then subjected to a steady shear stress of 20 dyne/cm(2) applied either parallel or perpendicular to the direction of the ridge/groove topography. HAECs subjected to flow parallel to the ridge/groove topography exhibited protagonistic effects of the two stimuli on cellular orientation and elongation. In contrast, flow perpendicular to the substrate topography resulted in largely antagonistic effects. Interestingly, the behavior depended on the shape and size of the topographic features. HAECs exhibited a response that was less influenced by the substratum and primarily driven by flow on isotropically ordered holed surfaces of identical pitch to the anistropically ordered surfaces of alternating ridges and grooves. Simultaneous presentation of biophysical cues to the basal and apical aspects of cells also influenced nuclear orientation and elongation; however, the extent of nuclear realignment was more modest in comparison to cellular realignment regardless of the surface order of topographic features. Flow-induced HAEC migration was also influenced by the ridge/groove surface topographic features with significantly altered migration direction and increased migration tortuosity when flow was oriented perpendicular to the topography; this effect was also pitch-dependent. The present findings provide valuable insight into the interaction of biologically relevant apical and basal biophysical cues in regulating cellular behavior and promise to inform improved prosthetic design.